Analysing the Potential Application of the Earned Value Management (EVM) in the Spanish Construction Industry – An Initial Review of the Dataset - Sutrisna, Monty; Pellicer, E.; Picornell, M.; Torres-Machl, C. (Research Publishing Services, 2013)
The Earned Value Management (EVM) is a fully integrated project cost-and-schedule controlsystem that can provide a quick overview of a construction project. The aim of this paper isto report the initial findings of a research project set to investigate the degree of applicationand development of the project management principles and techniques, including EVM, inSpanish contracting firms. Data was collected through a questionnaire survey distributedamong construction project managers with a final number of 56 questionnaires and 12 interviewswith senior managers from the Spanish construction industry. Despite the findings fromliterature review suggesting the management style of Spanish managers that generally putless emphasis on planning and favours reactive approaches to problem solving, this researchfinds that in large Spanish construction companies, customized but meticulous planning practicesexist mainly contextualised within well defined procedures and supported by relativelyappropriate training schemes. One of the main problems identified, however, is the lack ofcollaborative relationship of the project stakeholders. These findings confirmed the potentialbenefit of introducing the EVM as a robust and more universal standard in Spanish contractingfirms.